?KINETICS OF Mn2+ EXTRACTION IN THE ACIDIC CHLORIDE-D2EHPA-KEROSENE SYSTEM USiNG THE CONSTANT INTERFACIAL AREA STIRRED CELL TECHNIQUE - Biswas, R K; Habib, M A; Ali, M R; Haque, M Z (Biological Sciences - PJSIR, 1998)
Kinetics of the system (~=O.I kmol m') have been studied over a wide range of Mn2+concentration, pH, extractant concentration and temperature conditions using the constant interfacial area stirred cell technique. The reaction orders with respect to Mn2+, D2EHPA (di-2-ethylhexylphosphoric acid, H2R2) and H+ concentrations have been estimated to be +I, +1 and -I respectively. The value of the rate constant, k, has been evaluated to be 10.6534 m s' at lower investigated pH region. Kinetic data at higher pH region appear to be erroneous due to the instantaneous variation of interfacial pH. Temperature dependence data give Ea values of 76.5 and 8.7 kJ mol') at lower and higher temperature regions respectively. The values of tlS± and tlH± have been evaluated. An analysis of the kinetic data suggests that the reaction step at the interfaces: Mn2+ + HR2'(i) -7 [Mn(HR2)]+(i), is theslowest at lower temperature region, and at the higher temperature region, the diffusion of the species to the interface to occur the above reaction is the slowest step. The entropy of activation suggests that the above reaction occurs through an SN2 mechanism.